FINANCING THE POPULATION THROUGH THE SOCIAL INSURANCE SYSTEM (European Journal of Economics, Finance and Business Development, 2025)
Economic-statistical analyzes of each type of social insurance, the results of the software for the appointment and payment of pensions and allowances have been studied. The increase in the number of recipients of social benefits and the amount of material assistance provided to low-income families, as well as their financial sources, was mentioned in our country. For the implementation of the social insurance system, a certain amount of financial resources will be needed. Therefore, social funds are an integral part of any economic mechanism. It is known that in order to protect the needy sections of the population, there is a need to redistribute income in a certain order. The financial means of such redistribution is through social funds. Social funds, in turn, can be state or non-state. The ratio between the forms of social savings depends on many factors, first of all, on the national model of economic development.